Financial Transparency: A Systematic Literature Review and Bibliometric Analysis - Khoirul Solihin; Vip Paramarta; Farida Yuliati (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This study aims to assess the development and strategic direction of research on financial transparency and identify literature gaps, conceptual trends, and global collaboration patterns. Using a Systematic Literature Review (SLR) approach combined with bibliometric analysis based on Scopus data until July 13, 2025, this study utilized the PRISMA protocol and VOSviewer software to map relationships between variables, authors, institutions, countries, and keywords. The results show that financial transparency is a strategic issue that continues to grow, especially in developed countries such as the United States, the United Kingdom, and China, but contributions from developing countries are starting to increase. The topic is closely related to financial management, corporate governance, sustainability, and digital technology. This study is limited by the use of English-language literature and the focus on one main keyword, so the potential for selection bias remains. Practically, the findings provide a basis for formulating more effective and accountable financial disclosure strategies and strengthening institutional governance. Socially, this research contributes to the enhancement of public trust, the reduction of information asymmetry, and the strengthening of a more inclusive financial system, particularly in the context of developing countries.